A Brief Review of Traditional plants as Sources of Pharmacological interests - Mohiuddin AK (Open Journal of Plant Science - Peertechz Publications, 2019)
The knowledge base of pharmacy medicine is changing. Even five decades ago rural people used to visit kobiraj doctors for traditional medication mostly obtained from the roots and leaves of the remote plants (As seen in old dramas and movies). During 70's to 8o', a modern allopathy system taken over most of it and plant medicines were completely became obsolete. However, the Bangladeshi traditional medicine is a unique conglomerate of different ethnomedical influences. Due to the geographic location and sociocultural characteristics of the country, it involves traditionally rooted elements influenced by local indigenous people and close-by Indian Ayurveda and Unani medicine. Given its inexpensive, easily accessible and well-established health services, the use of traditional medicine is an integral part of public health services in Bangladesh with its providers being deeply embedded within the local community. Recent data suggest that the utilization of traditional medicine health services in Bangladesh is widespread and plays a crucial role in providing health care for poor people, people in rural areas and for tribal people Purpose of the study: An illustrated review of traditional Bangladeshi plants, their nature and their pharmacological use  Findings: A careful use of these plants can bring dramatic changes in the history of medicine, on the contrary abuse/misuse is just waste of money and also creates potential health hazards. The emerging use of plant derived medicines should have a proper quality control and system control of sales, distribution and use through strict vigilance. Materials and Methods: A comprehensive literature review, consulting books, technical newsletters, newspapers, journals, and many other sources are done with this review. Health professionals like qualified doctors, chemists, company professionals have given their useful suggestions. A few folk healers' shops are also visited to see the real situation includes their sales policy, misleading claims without valid references. Pharma company representatives are also interviewed who are selling herb medicines as white-collar business. Few students of mine helped me by their feedback from previous experiences in visiting rural areas and use of folk medicine there. The article comprises both plant medicine and plants used for pleasure by general people.